Dairy intakes in older Irish adults and effects on vitamin micronutrient status: Data from the TUDA study - Laird, Eamon; Cunningham, Conal; Molloy, Anne; Mc Carroll, Kevin (My University, 2016)
Consumption of dairy products has been associated with positive health outcomes including a lower risk of hypertension, improved bone health and a reduction in the risk of type 2 diabetes. The suggested dairy intake for health in older adults is three servings per day but recent analysis of the NHANES data for older adults reported 98% were not meeting these recommendations. No studies have investigated the consequences of such declines in the dairy intakes of Irish older adults and the subsequent effects on vitamin micronutrient status.
PUBLISHED
Keywords: NHANES data; NHANES data; Ageing